The effect of afforestation on water infiltration in the tropics: systematic review and meta-analysis - Ilstedt, Ulrik; Malmer, A.; Verbeeten, E.; Murdiyarso, Daniel (2007)
Soil water infiltration influences groundwater recharge and potential top soil loss by erosion, as well as the partitioning of runoff into slow flow and quick flow. The aim of the work presented here was to critically review studies of the effects of afforestation on infiltrability in the tropics, using a systematic review approach to select peer-reviewed articles published in English and French. We then applied meta-analysis to test the hypothesis that afforestation or the use of trees in agriculture increases infiltration capacity. After assessing titles and abstracts, on the basis of specified selection and quality criteria, four references remained, comprising 14 comparative experiments. The overall result of the meta-analysis was that infiltration capacity increased on average approximately three-fold after afforestation or planting trees in agricultural fields (95% confidence interval: 2.4–4.7). For the meta-analysis, the most common problems resulting in exclusion of otherwise relevant experiments were issues with the experimental design, and the absence of statistics (variances and replicates). Even considering the studies that were excluded in the meta analysis (a total of six), the low number of studies examining the effects of afforestation is a severe problem with respect to modelling and examining the underlying processes associated with the full range of different edaphic situations, different species and different methods of establishment.